Feasibility study of industrial projects using Simos’ procedure - Marzouk, Mohamed; Amer, Omar; El-Said, Moheeb (Journal of Civil Engineering and Management, 2013)
Feasibility study is conducted in a stage prior to design, procurement and construction stages in order to determine the viability of project undertaken by an investor. This helps investors to decide whether to proceed with the project or not. Multi-Criteria Decision Making (MCDM) process can be utilized in the feasibility study stage to avoid wrong decisions might cause undesired losses. In industrial projects, wrong decisions might lead to bankruptcy of crucial economic entities. Private investors might have good initiative and the capital to establish economically successful projects but they might either select the inappropriate type of industry that might turn the investment to a failure or might not include some important/crucial considerations into account. This paper presents a key-list of gathered factors that are considered the important factors and affect the selection of industrial projects. Importance, relative importance and weights of these factors are determined using Simos’ procedure. The key-list has been applied on five case-studies of industrial projects and a Weighted-Sum Model (WSM) has been selected as a MCDM technique in order to acquire their final preferences, rank them and consequently come-up with the most preferred/suitable alternative to be constructed. Then, a sensitivity analysis has been performed to determine the most critical criterion of the key-list. Additionally, several scenarios have been processed to verify that the most important criterion of the key-list does not necessarily be the most critical criterion. Moreover, the sensitivity analysis also determines the most critical measure of performance assembled from the five casestudies.